2007
DOI: 10.1111/j.1365-3156.2007.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: A view from beneath: Community Health Insurance in Africa

Abstract: SummaryThis paper presents an overview of the development of Community Health Insurance (CHI) in subSaharan Africa. In 2003, nearly 600 CHI initiatives were registered in a dozen countries of francophone West Africa alone. At regional level, coordination networks have been created in Africa with the aim to support and monitor the developments of this innovative model of health care financing. At national level, governments are preparing the necessary legal frameworks for CHI implementation. CHI is increasingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 7 publications
0
32
0
5
Order By: Relevance
“…The strong evidence that CBHI and SHI can improve financial protection and enhance service utilization patterns is especially critical in this respect, but the weaker evidence that CBHI and SHI can foster social inclusion is also important. Although this type of impact is not unexpected in the case of CBHI because of its community orientation, 38 it is more surprising in the case of SHI, which some claim underrepresents the informal sector. 39 Yet targeted policies in the Philippines and Thailand have shown that SHI can reach this sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong evidence that CBHI and SHI can improve financial protection and enhance service utilization patterns is especially critical in this respect, but the weaker evidence that CBHI and SHI can foster social inclusion is also important. Although this type of impact is not unexpected in the case of CBHI because of its community orientation, 38 it is more surprising in the case of SHI, which some claim underrepresents the informal sector. 39 Yet targeted policies in the Philippines and Thailand have shown that SHI can reach this sector.…”
Section: Discussionmentioning
confidence: 99%
“…Whether SHI and CBHI have the same potential impact in settings other than those where the studies were conducted is highly dependent on a particular country's socioeconomic, cultural and political context. 2,12,38,[42][43][44] This is illustrated by the few studies that showed negative impacts of SHI and CBHI on certain domains. Similarly, the review does not provide an answer to the question of whether SHI, CBHI or PHI is the optimal type of health financing mechanism, or of how it compares with tax-based systems -this is also highly dependent on context.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…The limited resources devoted toward health care limit the number of health facilities added to the inexistence of health insurance scheme (23). In such context, the cases of malignant hypertension and target organ damage are frequent (24).…”
Section: Differences In Risk From Hypertensionmentioning
confidence: 99%
“…The literature proposes the following strategies to address inequity, adverse selection and inadequate supply of health services and insurance: public funding to subsidise premiums, strategies to promote increased revenue collection from the "healthy and wealthy", and improved CBHI management and quality of care (Mills, Ataguba, Akazili, Borghi, Garshong, Makawia et al, 2012;Ndiaye, Soors, & Criel, 2007;Soors et al, 2010). Yet continued low rates of enrolment suggest these strategies have not been successfully implemented.…”
Section: Introductionmentioning
confidence: 99%